1997
DOI: 10.1007/bf01708554
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of commercial slides for detection of immunoglobulin G againstBartonella henselae by indirect immunofluorescence

Abstract: Four commercial slides were compared with in-house slides for the detection of immunoglobulin G (IgG) against Bartonella henselae in 58 healthy persons from a rural region by an indirect immunofluorescence assay. MRL-BA slides (MRL Diagnostics, USA) and Virion slides (Virion, Switzerland) with agar-derived Bartonella henselae showed IgG titers of > or = 1:256 in 44.8% and 51.7%, respectively, whereas Bion slides (Bios, Germany), MRL-Vero slides (MRL Diagnostics), and in-house slides with cell-associated Barton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
4
25
2
1
Order By: Relevance
“…The aim of our study was to compare the sensitivity and specificity of our in-house test to that of a recently available commercial test from FT. With CSD patients, our results confirm the previously reported high sensitivity of the FT serological test (29,48,55,65), whereas a lower sensitivity and significantly lower median IgG titers were found with our in-house test. Reactive IgM antibodies were rarely detected for CSD patients by either test, and these antibodies would thus appear to be of little use diagnostically, as previously mentioned (6,27,55,63).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The aim of our study was to compare the sensitivity and specificity of our in-house test to that of a recently available commercial test from FT. With CSD patients, our results confirm the previously reported high sensitivity of the FT serological test (29,48,55,65), whereas a lower sensitivity and significantly lower median IgG titers were found with our in-house test. Reactive IgM antibodies were rarely detected for CSD patients by either test, and these antibodies would thus appear to be of little use diagnostically, as previously mentioned (6,27,55,63).…”
Section: Discussionsupporting
confidence: 90%
“…It remains the most frequently used technique, and many laboratories have performed Bartonella serology using tests developed in-house, with reported sensitivities varying considerably, from nearly 100% to less than 30% (54). Commercially prepared antigen slides are now available for B. henselae and B. quintana serology (29,48,55,65), and in this report we compare the sensitivity and specificity of one of these tests with our in-house IFA test, which has been used by our laboratory for 10 years. We compared the abilities of the two tests to detect immunoglobulin G (IgG) and IgM antibodies in serum samples from patients known to have CSD (B. henselae), chronic bacteremia (B. quintana), or endocarditis (B. henselae and B. quintana).…”
mentioning
confidence: 99%
“…The sensitivity and specificity of the serological test used in this study were similar to those previously reported (32) and confirm the results of studies showing the high sensitivity of the IFA test for the diagnosis of CSD (44,46). We report a sensitivity of 86.8% at a cutoff titer of Ն64.…”
Section: Discussionsupporting
confidence: 90%
“…The sensitivity of serology varies from one laboratory to another, ranging from near 100% to less than 30% (43). Commercially prepared antigen slides are now available for B. henselae and B. quintana serology (18,20,34,39,44,46). Accurate diagnosis of CSD is necessary because the presentation and course of the disease may resemble more severe diseases such as malignant tumors or mycobacterial infections.…”
mentioning
confidence: 99%
“…Sera from 58 healthy blood donors (Swiss residents) served as control samples as published previously. 10 Positive IgG titres of greater than 1:256 were considered significantly elevated. 10 As routine genetic testing of patients and relatives is currently not yet available, the diagnosis of a familial form of ARVC was essentially based on the exact data of the patients as well as their family history.…”
Section: Methodsmentioning
confidence: 99%